Annulment of Marriage Because of Threats in Langsa City - Muhammaddiah, Muhammad Rusdi (State of Islamic Institute Langsa, 2022)
This article aims to answer questions regarding the consideration of the judges of the Langsa City Syar'iyyah Court in the Decision Number: 0101/Pdt.G/2016/Ms-Lgs considering the annulment of marriages due to threats. The research method of this research is the normative juridical method. The researcher obtains the primary data from the Decision of the Syar'iyyah Court of Langsa City Number: 0101/Pdt.G/2016/Ms-Lgs. Based on the results, then there are two conclusions can be drawn. First, the judge's consideration in deciding the case based on two factors, those are the consideration of facts and legal considerations as stipulated in Articles 24 and 25, and Article 27 paragraph (1) of Law Number 1 of 1974 concerning Marriage. Second, the Panel of Judges has also carried out a mediation process against the Petitioner and the Respondent, but in that case the Respondent was never present at the trial and a summons was made by the court properly and officially. Therefore, the Syar'iyyah Court of Langsa City decides to grant the Petitioner's claim and annul the marriage that had occurred and stated that the Marriage Certificate between the Petitioner and the Respondent had no legal force.